Path Under Construction: Challenges Beyond S-Framed Motion Event Construal in L2 German - Madlener-Charpentier, Karin; Liste Lamas, Elsa (Frontiers in Communication, 2022)
The encoding of motion events is known to be challenging for second language (L2) users, particularly if the lexicalization patterns of their first language (L1) diverge from those of the L2. This paper analyzes oral and written motion event descriptions produced by advanced L2 users of German, an information-dense satellite-framed language. Based on L2 usage and error patterns, we discuss six major challenges with respect to motion event and, more specifically, path encoding. These challenges clearly go beyond event construal and the acquisition of the basic satellite-framed lexicalization pattern (e.g., verb semantics) as well as beyond expected challenges related to the use of prepositional phrases (e.g., prepositional semantics, case marking). Advanced L2 users actually particularly struggle with “smaller” path encoding devices such as particles, locative and directional adverbs, their formal and functional differentiation, their usage patterns and combinatorial potential. These aspects seem to be challenging for advanced L2 users of German with either verb-framed L1s (French, Spanish) or satellite-framed L1s (Danish, English). We therefore discuss characteristics of the target language input that might explain why L2 users struggle with identifying and differentiating these path encoding devices, their usage and combinatorial patterns, as well as potential implications and options for L2 teaching.